(untitled) (Research, Society and Development, 2020)
Fishing activity is important in the economy of the coastal region in the State of Pará. In this context, there is the municipality of Augusto Correa, one of the main fishing landings. The municipality is one of the largest lobster exporting hubs in the State, however, few studies on other fisheries and species landed have been carried out and published, with this, we try to understand the fishing of the municipality. The applied methodology consisted of semi-structured interviews in the municipality’s ports for twelve months in 2018, with fishermen, masters and shipowners, using specific forms, providing information about the vessels and equipment, monitoring landings and analyzing documents related to production with the shipowners. With the data in hand, the main categories of active vessel and main equipment were characterized. We compared the monthly averages landed through analysis of variance (p <0.05); the main species that make up the landed fish community were also evaluated, thereby determining the faunal associations between them, based on the temporal variation of the landings, through the Cluster analysis cluster analysis. Small boats (BPP) were the main category of fishing vessel; the serreira net, being the main fishing gear, followed by the deep longline and manzuá; the serra Scomberomorus brasiliensis is the main species in abundance, and another twenty-eight species make up the structure of the ictic community; there were no significant differences between the average monthly productions (p = 0.99; p> 0.05). The grouping revealed the presence of eleven distinct fauna subgroups, consisting of species with similarities in landings over time.